THE VALIDITY OF CUBE AND BLOCK MATERIAL LEARNING DEVICES USING A REALISTIC MATHEMATICS EDUCATION (RME) APPROACH - Eka Fuji Astuti; Sri Rezeki (Mathematics Research and Education Journal, 2023)
Learning devices are tools designed by teachers to facilitate teachers in carrying out the learning process so that they can support the achievement of the expected success of learning activities. The purpose of this development research is to produce learning device products in the form of Learning Implementation Plans (RPP) and Student Worksheets (LKPD) on valid flat-sided geometric shapes using the Realistic Mathematics Education (RME) approach. This type of research is development research with the ADDIE model, which has been modified into three stages (Analysis, Design, and Development) without the Evaluation and Implementation stages. The instrument for collecting research data is learning device validation sheets in the form of lesson plans and worksheets. The data analysis used is descriptive data analysis which describes the level of validity of the product with data obtained from the results of validation by four experts. Validation activities were carried out in Pekanbaru City from August 5, 2020, to September 2, 2020, with the research results obtained in the form of an RPP validation result of 96.09 with very valid criteria and an LKPD validation result of 90.52 with very valid criteria.